Sistem Kontrol dan Monitoring: Sterilisasi Micro-organism Pada Ruangan Pasien Rawat Inap Untuk Menurunkan Penyakit Menular - M. Najib Fikri Fadillah; Mulyadi, Adi (Journal Electric Field, 2025)
Sterilization rooms are a concern for patients in hospitals. Inpatients affected by infectious diseases require a special action room. Therefore, the application of the sterilization room control and monitoring system with IoT is proposed to overcome TB patients. The study technique covers the design and testing of the control system and IoT monitoring system with time variations of 60, 90, and 120 minutes. The results of the application of the control system application show that the time variation causes a decrease in current from 0.8A to 0.5A with a test time of 60 minutes, but inversely proportional to the voltage with a test time of 90 and 120 minutes, which increases by 3.2V-3.9V. While the results of monitoring data in the inpatient room have varying lag times ranging from 0.13 seconds, 0.8 seconds and 0.7 seconds. the average value of time variation and data transmission affects the decrease in the bacteria of the hospital room cleaning process. the longer the irradiation time, the number of bacteria will decrease. Sterilizer control and monitoring system is used as a recommendation for infectious diseases in the inpatient room in the hospital.